Inflammatory cytokines and immune system modulation by aerobic versus resisted exercise training for elderly - Abd El-Kader, Shehab M; Al-Shreef, Fadwa M (African health sciences, 2018)
Background: Aging is characterized with immunosenescence associated with a hyper-inflammatory state, characterized by elevated circulating levels of pro-inflammatory mediators. Physical exercise is a potential strategy for improving the immune system dysfunction and chronic inflammation that accompanies aging. However, there is a need to differentiate between aerobic and resistance exercise training regarding human immune system and systemic inflammation among the elderly Saudi population. Objective: The aim of this study was to compare the impact of 6 months of aerobic versus resisted exercise training on inflammatory cytokines and immune system response among elderly. Material and methods: Sixty previously sedentary elderly subjects participated in this study, their age ranged from 61- 66 years. All Subjects were randomly assigned to supervised aerobic exercise intervention group (group A, n=40) or resistance exercise group (group B, n=40). Number of CD3+,CD4+,CD8+ T cells count and CD4/CD8 ratio were quantified, IL-6, TNF-α and IL10 were measured before and after 6 months, at the end of the study. Results: The mean values of CD3+, CD4+ and CD8+ T cells count and IL-10 were significantly increased, whereas the mean values of CD4/CD8 ratio,IL-6 and TNF-α were significantly decreased in group (A) and group (B). Also; there were significant differences between mean levels of the investigated parameters in group (A) and group (B) after treatment. Conclusion: The current study provides evidence that aerobic exercise is more appropriate in modulating the immune system and inflammatory markers among the elderly population.